Successful Laparoscopic Cholecystectomy of Giant Gallstone – A Case Report Study - Saman Taher Barzinjy (Diyala Journal of Medicine, 2024)
Background: Gallstone diseases are the most common biliary pathologies. They are very frequent in the Western world, where the approximate incidence is about 10–15%. Laparoscopic cholecystectomy is the method of choice for treating gallstone disease. The conversion rate of laparoscopic to open surgical procedures is estimated to be about 4%- 5%. Gallstone size is important since large/giant gallstones are more liable for technical difficulties during laparoscopic interventions. Objective: The aim is to present the rare case of a giant gallstone removed laparoscopically. Case presentation: A female of 53 years old presented to the private clinic for on-and-off signs and symptoms of gallstone diseases throughout the previous 3 years; investigation revealed a large gallbladder stone (4 cm in maximum diameter). Laparoscopic cholecystectomy has been performed for an adhesive gallbladder without the need for conversion to the open classical method and without complications; the gallstone size measured after retrieval was about 4 cm in length. Conclusion: Giant or large gallstones carry a significant risk of complications. Even in these challenging cases, laparoscopic cholecystectomy is regarded as the preferred treatment option over open cholecystectomy. Highly skilled and experienced laparoscopic surgeons should perform the procedure to ensure successful outcomes. The possibility of converting to an open procedure in case of failure to expose the clear anatomy and any intraoperative technical difficulties should be considered. Keywords: Giant gallstone, gallstone disease, large gallstone, laparoscopic cholecystectomy.